Sistem Monitoring Dan Kontrol Otomatis LPJU Dengan Komunikasi Lora - Yudhi, Yudhi; Surojo, Surojo; Bhaihaki, Fahrul; Mutialisa, Lulu (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Public Street Lighting (LPJU) is a source of lighting that helps road users when crossing the road at night. But there are still many LPJUs that light up during the day in the absence of a control system. Therefore, this study will discuss the LPJU automatic monitoring and control system using LoRa as a remote communication device. The methodology on this system uses LDR sensors as input and is processed by esp32 devkit v1 with lora communication as data transmission, and the monitoring system uses the website display on localhost phpmyadmin. The results of LoRa communication testing in LOS conditions with a distance of 100 m to 2000 m were successfully sent and received well from LPJU to a laptop even though there was a delay in data reception, while in Non-LOS conditions LoRa communication was less than optimal because there were delays and obstructions when receiving data with a distance of 1 meter to 30 meters. LPJU can be activated and disabled automatically using LDR as an automatic salkar contact, and monitoring results can be displayed on a website page with an internet connection.